BENTUK DESAIN PRODUK KRIYA DARI LIMBAH KAYU PADA PRODUK CENDERAMATA - Washinton, Rahmad; Ranelis, Ranelis; Malik, Kendall; Yandri, Yandri; Alipuddin, Alipuddin (SPACEPRO: Product Design Jurnal, 2023)
The research entitled "Design Motifs and Craft Products from Wood Waste in Souvenir Products" aims to utilize wood waste in the form of sawdust obtained during the process of carving and making products. The method used is experimental, the research procedure carried out is by means of exploration and design. Exploration aims to find ideas or concepts through data mining and literature studies, observations and interviews. The data that has been collected is processed and analyzed qualitatively then presented verbally, later becoming the basis for conducting design experiments. Design is the embodiment of ideas and concepts resulting from exploration into souvenir product designs. In studying product development and techniques, we use design strategy studies consisting of design strategies and innovation strategies proposed by Agus Sachari, and other theories consisting of the appeal of beauty. product, materials used, tools used, manufacturing techniques and product authenticity. Keywords: Wood waste, products, crafts.